FEATURES OF SONGS THAT SUPPORT THE DEVELOPMENT OF PRONUNCIATION SKILLS - Boboyorova Mehrigul; Zulfiya Axmedova (TADQIQOTLAR, 2026)
Annotation: This paper explores the role of songs in facilitating the learning of English pronunciation. It examines the specific characteristics of songs, such as rhythm, melody, repetition, and stress patterns, that help learners improve their pronunciation skills. By analyzing both theoretical perspectives and practical classroom applications, the study highlights how integrating music into language teaching can enhance learners’ phonetic accuracy, intonation, and overall spoken fluency. The research also emphasizes the motivational and cognitive benefits of using songs, demonstrating that engaging with music supports both auditory perception and speech production in second language acquisition.